2016
DOI: 10.1111/jiec.12384
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Environmental Footprint of Urban Food Consumption

Abstract: Summary Assessments of urban metabolism (UM) are well situated to identify the scale, components, and direction of urban and energy flows in cities and have been instrumental in benchmarking and monitoring the key levers of urban environmental pressure, such as transport, space conditioning, and electricity. Hitherto, urban food consumption has garnered scant attention both in UM accounting (typically lumped with “biomass”) and on the urban policy agenda, despite its relevance to local and global environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 92 publications
(181 reference statements)
0
51
0
Order By: Relevance
“…Cities can be considered as living organisms, driven by material and energy flows (González-García, Manteiga, Moreira, & Feijoo, 2018a). Modern cities can neither meet the demand for bulk resources nor assimilate their residues within their limits (Goldstein, Birkved, Fernández, & Hauschild, 2017), and urban metabolism (UM) is therefore an important framework with which to assess the demand for resources and generation of waste in cities, although the social and economic dimensions are highly complex and not well integrated into UM assessments (Chester et al, 2012). UM is a concept that was introduced by Burgess (1925) to analyze urban growth from a sociologist's perspective.…”
mentioning
confidence: 99%
“…Cities can be considered as living organisms, driven by material and energy flows (González-García, Manteiga, Moreira, & Feijoo, 2018a). Modern cities can neither meet the demand for bulk resources nor assimilate their residues within their limits (Goldstein, Birkved, Fernández, & Hauschild, 2017), and urban metabolism (UM) is therefore an important framework with which to assess the demand for resources and generation of waste in cities, although the social and economic dimensions are highly complex and not well integrated into UM assessments (Chester et al, 2012). UM is a concept that was introduced by Burgess (1925) to analyze urban growth from a sociologist's perspective.…”
mentioning
confidence: 99%
“…• Supporting Information S1 demanding agri-food in cities, such as commercial establishments (i.e., restaurants and hotels) and foodprocessing industries, often go ignored and unquantified entirely-an important oversight in cities where residents might not be the predominant users (Goldstein et al, 2016).…”
Section: 1029/2018ef001048mentioning
confidence: 99%
“…Cities have also started to recognize that urban demand for FEW has far-reaching environmental impacts both within and outside city boundaries. In an analysis of over 200 urban metabolism studies, 100 cities were found to have included the trans-boundary embodied energy of food production in their carbon accounts (Goldstein et al 2016). The above examples illustrate that cities are increasingly interested in quantifying the impact of their FEW supplies on the larger environment, as well as in reverse, the risk posed by the environment on their supplies.…”
Section: Introductionmentioning
confidence: 99%
“…First, methods must be clarified for quantifying community-wide FEW demand by homes, visitors, businesses and industries. A review by Goldstein et al (2016) notes that cities have previously used ad hoc methods, often only capturing residential food demand, but not that of visitors or food processing industries, thus the authors concluded that 'urban foodprint was underestimated in studies where the scope of urban metabolic activities beyond the household boundary were excluded ' . Because city policies have potential to address diverse actors within their jurisdiction (homes, businesses, and industries), developing methods to assess FEWdemand by all three user-categories is important.…”
Section: Introductionmentioning
confidence: 99%